Muslim women in the mirror: the stigma of Muslim women in Poland - Stojkow, Maria (Wydawnictwa AGH, 2019)
The main objective of the paper is to recreate a strategy to deal with the stigma in the daily lives of Muslim women who decided to move permanently to Poland, and Polish women who decided to convert to Islam. The subject of the research is Muslim women who live in Poland and participated in biographical interviews. According to the interviews, an image of Muslim women based on what they themselves think was reconstructed. Their methods of dealing with everyday situations, which these women face in the country in which they live, and conflicts with their families of origin, are presented. In Poland, as shown by opinion polls, people originating from Muslim countries are perceived negatively. As a result, immigrants from these regions who stay in our country are stigmatised as the other, different, hostile and dangerous to the society. This is the result of commonly shared negative stereotypes. A very similar fate is experienced by Polish women who have converted to Islam. Living with stigma forces those stigmatised to adopt strategies that allow them to operate in a foreign country. This situation is particularly oppressive for Muslim women, who on the one hand must deal with the stigma they carry due to their otherness in the host country, while on the other hand must follow tradition and constraints imposed by the religion and culture in which they were raised. Muslim clothing allows fast and easy categorization. Women wearing hijabs are easily identified, and because of it possible stereotypes and prejudices are activated.

Głównym celem artykułu jest odtworzenie strategii radzenia sobie ze stygmatyzacją w codziennym życiu muzułmanek, które zdecydowały się na stałe przenieść do Polski, oraz kobiet mieszkających na stałe w Polsce, które zdecydowały się przejść na islam. W artykule oparto się na wywiadach biograficznych przeprowadzonych z muzułmankami mieszkającymi w Polsce, tak by zobrazować ich sytuację społeczną. W Polsce, jak pokazują badania opinii publicznej, ludzie pochodzący z krajów muzułmańskich są postrzegani negatywnie. W rezultacie imigranci z tych regionów, którzy przebywają w naszym kraju, są napiętnowani jako inni, różni, wrodzy i niebezpieczni dla społeczeństwa. Jest to wynikiem powszechnych negatywnych stereotypów. Bardzo podobny los spotkał Polki, które przeszły na islam. Życie z piętnem zmusza do przyjmowania strategii, które pozwalają działać w obcym kraju. Sytuacja ta jest szczególnie uciążliwa dla muzułmańskich kobiet, które z jednej strony muszą uporać się z piętnem, które niosą ze względu na swoją odmienność w kraju przyjmującym, a z drugiej strony muszą przestrzegać tradycji i ograniczeń narzuconych przez religię i kulturę, w której były wychowane. Istotny jest również fakt, iż damski strój muzułmański umożliwia szybką i łatwą kategoryzację. Kobiety noszące hidżaby czy nikaby są łatwe do zidentyfikowania i dlatego narażone są na stereotypowe traktowanie i uprzedzenia.
Muzułmanki w zwierciadle społecznym: stygmat bycia muzułmanką w Polsce
Studia Humanistyczne AGH
Keywords: stigma; Muslim women; stereotypes; prejudices; stygmatyzacja; muzułmanki w Polsce; stereotypy; uprzedzenia